The Effect of Debtor Character and Fiducian Guarantee from SME Entrepreneurs on Credit Approval - BINTANG, Ida Ayu Made; SURASMI, Ida Ayu; KAWISANA, Putu Gede Wisnu Permana (Journal of Entrepreneurial and Business Diversity, 2023)
Purpose:This study aims to determine the effect of debtor character and fiduciary guarantees from SME entrepreneurs on credit approval during the coronavirus pandemic at Bank BPD Klungkung Regency. The location of this research is at the BPD Bank, Klungkung Regency.Methodology:The population used is the credit employees of Bank BPD Klungkung Branch, with 35 employees. The sample in this study used 35 respondents. The data collection technique used in this study was a questionnaire containing a Likert scale. The data analysis technique used is multiple linear regression analysis.Findings:The results of this study indicate that the debtor's character has a significant positive effect on credit approval during the coronavirus pandemic at Bank BPD Klungkung Regency. Fiduciary guarantees from SME entrepreneurs have no significant positive effect on credit approval during the coronavirus pandemic at Bank BPD Klungkung Regency.Implication:This indicates that banks prioritize easy credit for SME entrepreneurs rather than fiduciary guarantees in supporting credit relaxation policies during the Covid-19 pandemic.